Printed Riddles in Early Modern Italy: Traditional Perspectives and New Approaches - Marco Francalanci (Journal of Early Modern Studies)
The purpose of the article is to draw attention to Italian riddles of the Renaissance. This publishing and literary genre has been studied especially from ethnological or literary perspectives. What is completely lacking, however, are studies that deal with how this literature was produced, how it circulated and who printed it. These perspectives are highly relevant: they make us realise that such texts were not only produced by the likes of Cervantes, Bembo or Shakespeare, but that riddles were often written, performed and printed by men who are now forgotten, sometimes not fully literate and often not from elites. The intention here is to place these writings in a methodological and historiographical framework that may lead to more in-depth study in the future.